Study on Effects of Hand-arm Vibration Syndrome on Construction Workers in Oman (International Journal of Occupational Safety and Health, 2024)
Introduction: The prolonged exposure of construction industry workers to various vibrating equipment gives rise to hand-arm vibration syndrome (HVS). Due to its growing incidence among construction workers, researchers have sought to examine its presence, prevalence, and potential impacts in various locations across the world.  Therefore, the main objective of this paper is to examine the effects of hand-arm vibration syndrome on construction workers in selected construction sites in Oman.Methods: This study used a quantitative cross-sectional design approach to achieve the study objective. A Google form questionnaire consisting of 18 questions was distributed to gather, analyze, and sample the responses of 40 construction workers.Results: The results revealed that the workers at the selected construction site are largely young, between the ages of 20-25 (38% of the responses), and able-bodied males (100%) who displayed full knowledge and awareness of the nature, symptoms, and effects of hand-arm vibration syndrome. The most common symptoms of hand-arm vibration syndrome were vibration of white fingers, painful numbness in hands and arms, and musculoskeletal pains, as reported by 72% of the workers, whereas pain and sleep disturbance, reduced or inability to do work safely in cold conditions were termed the most prominent effects of hand-arm vibration syndrome.Conclusion: In conclusion, the study findings support the potential for an effective elimination or reduction of hand-arm vibration syndrome in construction work environments by the implementation of good occupational safety and personal health procedures. The findings of the study also underline other preventive measures that could help tackle the challenges posed by hand-arm vibration syndrome, thus underpinning the study's objective